Evaluation of a silicon carbide P–N diode for thermal neutron detection in a radiotherapy LINAC - Martín Pérez; Felipe Zamorano; Celeste Fleta; Carles Muñoz-Montplet; Diego Jurado-Bruggeman; Marcio Jiménez; Pablo Guardia; Gina Grabulosa-Morera; Roger Morales-Pérez; Gemma Rius; Philippe Godignon; Giulio Pellegrini; et al. (Scientific Reports)
Abstract Accurate neutron detection in mixed photon-neutron and pulsed radiation fields is technically challenging, impacting industrial and medical applications. This paper presents the first measurements of thermal neutrons in conventional radiotherapy accelerators using a silicon carbide (SiC) P–N diode with different neutron converters. SiC detectors enable real-time estimation of secondary thermal neutron contributions, crucial for emerging radiotherapy techniques requiring precise neutron fluence monitoring. Beyond medical applications, the presented detectors show potential for neutron dosimetry, radiation monitoring, nuclear safety, and scientific research. The SiC diode active detection layer is less than 30 µm thick, and provides excellent gamma rejection ( $$5× 10^{-8}$$ ), allowing discrimination of neutrons-induced events in mixed radiation fields. Experimental tests conducted on a TrueBeam radiotherapy LINAC demonstrated a thermal neutron detection efficiency of (4.32 ± 0.02)% for a (50 ± 10) µm thick $$^6$$ LiF neutron converter. The detector, placed at 1.2 m from the accelerator isocenter, was used to measure neutron fluences at different monitor unit (MU) rates, ranging from 100 to 600 MU/min, with the LINAC operating at 15 MV. Under these conditions, the detector exhibited good linearity, without saturation or dead time effects.